2006
DOI: 10.2320/matertrans.47.194
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Mechanical Properties of Cu–Zr–Al–Sn Bulk Metallic Glasses

Abstract: Formation and mechanical properties of Cu-Zr-Al-Sn bulk metallic glasses were investigated. The glass-forming ability of Cu 50 Zr 50 alloy is significantly improved with addition of Al, and the critical diameter for glass formation increases from 2 to 7 mm for

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…3 and 4 for the Young's modulus, E, and the hardness, H v , respectively. The data have been collected from various sources [3,[12][13][14][15][16][17][18][19][20][21][22][23][24]. They encompass practically all known metallic glasses obtained both in ribbon and bulk form.…”
Section: Relationship Of Mechanical Properties and Thermal Propertiesmentioning
confidence: 99%
“…3 and 4 for the Young's modulus, E, and the hardness, H v , respectively. The data have been collected from various sources [3,[12][13][14][15][16][17][18][19][20][21][22][23][24]. They encompass practically all known metallic glasses obtained both in ribbon and bulk form.…”
Section: Relationship Of Mechanical Properties and Thermal Propertiesmentioning
confidence: 99%
“…Recently, much attention has been paid to the Cu-Zr-based metallic glasses [7][8][9][10], due to their simple composition, innocuous and free of noble elements, large GFA, and wide composition range. Research has demonstrated that element addition and displacing is an efficient way to prepare BMG with better GFA [3,[10][11][12][13][14][15]. The ternary Cu-based BMGs were first reported in Cu-Zr-Ti and Cu-Zr-Al alloy systems by Inoue group [8,16].…”
Section: Introductionmentioning
confidence: 98%
“…Bulk Cu 50 Zr 42 Al 8 amorphous samples with 4-4.5 mm in diameter were successfully prepared by copper mold suck casting [4][5]. The GFA and properties of Cu-Zr-Al amorphous alloys can be enhanced by substituting Y [6][7], Nb [8][9][10][11], Ag [12][13], Be [13], Er [14], Sm [14], Sn [15], Gd [16][17], La [17], Ce [17], and Nd [17] for Zr. More excellent effect about rare-earth elements on the GFA and properties of bulk Cu-Zr-Al amorphous alloys and wide application in the industrial casting process can be expected.…”
Section: Introductionmentioning
confidence: 99%